Inhibition of mTORC1 by lncRNA H19 via disrupting 4E-BP1/Raptor interaction in pituitary tumours. Issue 1 (December 2018) - Wu, Ze; Yan, Lichong; Liu, Yan; Cao, Lei; Guo, Yu; Zhang, Yong; Yao, Hong; Cai, Lin; Shang, Han; Rui, Wei; Yang, Gang; Zhang, Xiao; et al.
Abstract Aberrant expression of long noncoding RNA H19 has been associated with tumour progression, but the underlying molecular tumourigenesis mechanisms remain largely unknown. Here, we report that H19 expression is frequently downregulated in human primary pituitary adenomas and is negatively correlated with tumour progression. Consistently, upregulation of H19 expression inhibits pituitary tumour cell proliferation in vitro and tumour growth in vivo. Importantly, we uncover a function of H19, which controls cell/tumour growth through inhibiting function of mTORC1 but not mTORC2. Mechanistically, we show that H19 could block mTORC1-mediated 4E-BP1 phosphorylation without affecting S6K1 activation. At the molecular level, H19 interacted with 4E-BP1 at the TOS motif and competitively inhibited 4E-BP1 binding to Raptor. Finally, we demonstrate that H19 is more effective than cabergoline treatment in the suppression of pituitary tumours. Together, our study uncovered the role of H19-mTOR-4E-BP1 axis in pituitary tumour growth regulation that may be a potential therapeutic target for human pituitary tumours. LncRNA H19 has been shown to be aberrantly expressed in different cancers. Here, the authors show that H19 lncRNA is downregulated in pituitary adenomas and H19 is able to impede pituitary tumorigenesis via disruption of 4E-BPB1 and Raptor interaction to inhibit the phosphorylation of 4E-BP1.